RNAi-Mediated Reverse Genetic Screen Identified Drosophila Chaperones Regulating Eye and Neuromuscular Junction Morphology. Issue 7 (1st July 2017) - Raut, Sandeep; Mallik, Bhagaban; Parichha, Arpan; Amrutha, Valsakumar; Sahi, Chandan; Kumar, Vimlesh
Abstract: Accumulation of toxic proteins in neurons has been linked with the onset of neurodegenerative diseases, which in many cases are characterized by altered neuronal function and synapse loss. Molecular chaperones help protein folding and the resolubilization of unfolded proteins, thereby reducing the protein aggregation stress. While most of the chaperones are expressed in neurons, their functional relevance remains largely unknown. Here, using bioinformatics analysis, we identified 95 Drosophila chaperones and classified them into seven different classes. Ubiquitous actin5C -Gal4-mediated RNAi knockdown revealed that ∼50% of the chaperones are essential in Drosophila . Knocking down these genes in eyes revealed that ∼30% of the essential chaperones are crucial for eye development. Using neuron-specific knockdown, immunocytochemistry, and robust behavioral assays, we identified a new set of chaperones that play critical roles in the regulation of Drosophila NMJ structural organization. Together, our data present the first classification and comprehensive analysis of Drosophila chaperones. Our screen identified a new set of chaperones that regulate eye and NMJ morphogenesis. The outcome of the screen reported here provides a useful resource for further elucidating the role of individual chaperones in Drosophila eye morphogenesis and synaptic development.